Derteminan Permintaan Produk Fast Fashion di Kota Pekanbaru - Teuku Johansyah; Mardiana; Indri Yovita (Yayasan Lentera Avanya Nagari, 2026)
This study aims to analyze the determinants of fast fashion product demand in Pekanbaru. The variables examined include price (X1), income (X2), and age (X3). This research utilizes a quantitative approach, with data collection conducted with data collected through questionnaires distributed to 70 respondents selected using a purposive sampling method. The data analysis technique used is multiple linear regression, assisted by SPSS statistical software. The results indicate that simultaneously and partially, the variables of price (X1), income (X2), and age (X3) have an effect on the demand for fast fashion products in Pekanbaru (Y). The coefficient of determination (Adjusted R²) of the regression model is 48.9%. This means that the independent variables can explain 48.9% of the variance in demand, while the remaining 51.1% is explained by other variables not examined in this study. Among the three variables, income (X2) is the most dominant factor influencing demand. These findings suggest that consumer decisions in purchasing fast fashion products are more heavily influenced by monthly income.